The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/9750135
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment with Locoregional Flap for the Nose

Abstract: Nonmelanotic skin cancers (NMSCs) are the most frequent of all neoplasms and nasal pyramid represents the most common site for the presentation of such cutaneous malignancies, particularly in sun-exposed areas: ala, dorsum, and tip. Multiple options exist to restore functional and aesthetic integrity after skin loss for oncological reasons; nevertheless, the management of nasal defects can be often challenging and the best “reconstruction” is still to be found. In this study, we retrospectively reviewed a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…For many cancer types, such as some hematologic tumors, chemotherapy is the most effective treatment ( Mousavi et al, 2016 ; Bell et al, 2018 ). For other types, surgery is the best option ( Marcasciano et al, 2017 ; Ye et al, 2017 ); when surgery is not possible, chemotherapy can be helpful in stopping tumor growth or reducing its volume ( Wagner et al, 2017 ; Wang et al, 2018 ). Unfortunately, in many cases antitumor drugs are not effective and they often have deleterious side effects ( Iwamoto et al, 2014 ; Li and Caeyenberghs, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For many cancer types, such as some hematologic tumors, chemotherapy is the most effective treatment ( Mousavi et al, 2016 ; Bell et al, 2018 ). For other types, surgery is the best option ( Marcasciano et al, 2017 ; Ye et al, 2017 ); when surgery is not possible, chemotherapy can be helpful in stopping tumor growth or reducing its volume ( Wagner et al, 2017 ; Wang et al, 2018 ). Unfortunately, in many cases antitumor drugs are not effective and they often have deleterious side effects ( Iwamoto et al, 2014 ; Li and Caeyenberghs, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction with locoregional flaps was performed in all cases. Accurate evaluation of the patients clinical condition and local defect should be always considered in order to select the best surgical option [1].…”
Section: Resultsmentioning
confidence: 99%
“…The search of the literature revealed that satisfactory reconstruction of the columella is possible through several techniques (Marcasciano et al, ; Margulis et al, ). For skin‐only columellar defects, skin grafts are a reasonable reconstructive method.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the reconstructive method should also address a color match and texture, minimizing donor site morbidity. The search of the literature revealed that satisfactory reconstruction of the columella is possible through several techniques (Marcasciano et al, 2017;Margulis et al, 2013). For skin-only columellar defects, skin grafts are a reasonable reconstructive method.…”
Section: Discussionmentioning
confidence: 99%